Sleep duration and daytime napping in relation to incident inflammatory bowel disease: a prospective cohort study. Issue 5 (9th November 2022) - Yuan, Shuai; Sun, Yuhao; Tan, Xiao; Geng, Jiawei; Sun, Jing; Chen, Xuejie; Yu, Lili; Wang, Jiayi; Zhou, Xuan; Hesketh, Therese; Larsson, Susanna C.; Chen, Jie; et al.
Summary: Background: Sleep dysregulation has been linked to gastrointestinal dysfunction and inflammation. Aims: To explore the associations between sleep duration, daytime napping and inflammatory bowel disease (IBD), Crohn's disease (CD) and ulcerative colitis (UC). Methods: Exposure information was obtained from the baseline questionnaire. Sleep duration was coded as continuous and categorical (≤5, 6, 7, 8, ≥9 h/day) variables. Daytime napping was defined as yes (sometimes/usually) and no (never/rarely). Incident IBD cases were defined from primary care and hospital inpatient records. Polygenic risk scores (PRS) for the outcomes were constructed and categorised into low, intermediate and high risk. Hazard ratio (HR) and confidence interval (CI) were estimated using Cox proportional hazard regression. Results: The analysis included 2604 incident IBD cases (806 CD and 1798 UC) with a median follow‐up of 12.0 years. Comparing sleep duration ≤5 with 7 h/day, the HR of IBD, CD and UC was 1.36 (95% CI, 1.17–1.59), 1.53 (95% CI, 1.17–2.00) and 1.29 (95% CI, 1.07–1.56), respectively. Comparing participants with and without daytime napping, the HR of IBD, CD and UC was 1.13 (95% CI, 1.05–1.23), 1.25 (95% CI, 1.08–1.44) and 1.09 (95% CI, 0.90–1.20), respectively. No interaction of sleep duration and daytime napping with PRS was detected.  However, the associations appeared stronger in individuals with high rather than low PRS. Conclusions: This study reveals positive associations between short sleep duration and daytime napping and IBD risk. Abstract : Short sleep duration and daytime napping increased risk of inflammatory bowel disease.